Influence of steckling transplanting dates on heat-unit requirement of bolting and subsequent seed yield and quality of Asiatic carrot (Daucus carota) - NAGARAJAN, SHANTHA; PANDITA, VINOD K; SINHA, S N (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during 1996-97 and 1997-98 to study the relationship between accumulated growing degree-days (GDD) and bolting behaviour of 'Pusa Kesar' Asiatic carrot (Daucus carota L.) and its subsequent effect on seed production and quality. Among the 6 environments studied, large variation was observed in the accumulated calendar days (23.8%) and moderate variation in GDD (12.7%) during the period between transplanting and 50% bolting. The heat unit accumulated bctween 50% bolting and harvest had significant positive correlation with seed yield and quality traits. To get optimum seed yield of good quality in Asiatic carrot, minimum 2 200 heat units were required to be accumulated between transplanting and harvest.